(3eNJGQ GdCZGfj aj GdCNHGQ hGdJgGfjs - (3eMeO Hf ecQe Hf Ydj, CHh GdaVd, LeGd GdOjf GHf efXhQ GdCfUGQj GdQhjaYj GdEaQjbj, J (B711 (3g` s
(3ChdgG (B:s
(3NhjdO, CHhPDjH GdgPdj(B: (3gh NhjdO Hf NGdO Hf eMQK Hf RHjO Hf eNRhe Hf gPjd s
(3BNQgG (B:s
(3eHJhQ hBNQ eG ajg(B: (3hcGf GdCbjTQ dG jSCd CMOkG CcKQ ef NeSI OQGge aCJi jhekG ef GdCjGe HjJ Mfjf GdNqeGQ GdPj cGf jCJjg ade jUGOag, aLYd jfJXQg aONdJ s
(3fSNI KGfjIs
(3GdLRA GdKGfj(B: (3Chdg MQa GdNGA GdeYLeIs
(3HChdgG agQS GdeJQLejfs
(3hHgG fXGe GdJYbjHI s
(3gPg GdfSNI efbhdI Yf GdfSNI GdChdi OGQ GdcJH GdeUQjI (B- (3GdJjehQjIs
2313 (3JGQjN jJfSjbgG hfXGe UaMGJgG Ch Cf GdfSNI GdChdi fbdJ efgG s
Keywords: (3GdCOHs